2008
DOI: 10.1093/biolreprod/78.s1.206a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Arachidonic Acid on the Reproductive Physiology of Female Atlantic Cod (Gadus morhua L.).

Abstract: a b s t r a c tThe present study was designed to investigate potential effects of arachidonic acid (ARA) on the reproductive physiology of female Atlantic cod (Gadus morhua L.).Two-year old Atlantic cod of both sexes were equally distributed into eight sea cages after completion of their first spawning in May 2005. Four experimental groups were established and fed diets with different levels of ARA corresponding to 0.5, 1, 2 and 4% of total fatty acid. Ovarian growth and development was documented every month.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…From these studies, the suggested optimal ARA doses in broodstock diets were varying substantially from as little as 0.6% d.w. (3.6% TFA) in Japanese flounder up to 1.6%–2.1% d.w. (13.2%–16.3% TFA) in blue gourami. A dose‐dependent response of dietary ARA inclusion was also observed in some species, such as Japanese flounder 135 and Atlantic cod 141 . In pikeperch ( Sander lucioperca ), an ARA dietary level of only 3.0% TFA negatively impacted on the egg quality, 142 which was attributed by the authors to the altered ARA/EPA ratio.…”
Section: Functions Of Ara In Fishmentioning
confidence: 69%
See 3 more Smart Citations
“…From these studies, the suggested optimal ARA doses in broodstock diets were varying substantially from as little as 0.6% d.w. (3.6% TFA) in Japanese flounder up to 1.6%–2.1% d.w. (13.2%–16.3% TFA) in blue gourami. A dose‐dependent response of dietary ARA inclusion was also observed in some species, such as Japanese flounder 135 and Atlantic cod 141 . In pikeperch ( Sander lucioperca ), an ARA dietary level of only 3.0% TFA negatively impacted on the egg quality, 142 which was attributed by the authors to the altered ARA/EPA ratio.…”
Section: Functions Of Ara In Fishmentioning
confidence: 69%
“…A dose-dependent response of dietary ARA inclusion was also observed in some species, such as Japanese flounder 135 and Atlantic cod. 141 In pikeperch (Sander lucioperca), an ARA dietary level of only 3.0% TFA negatively impacted on the egg quality, 142 which was attributed by the authors to the altered ARA/EPA ratio.…”
Section: Ara Requirements In Fingerling Juvenile and Adult Fishmentioning
confidence: 96%
See 2 more Smart Citations
“…The importance of arachidonic acid (ARA) in fish reproduction has been widely demonstrated in several species such as European sea bass Dicentrarchus labrax (Bruce et al, ), Japanese flounder Paralichthys olivaceus (Furuita, Yamamoto, Shima, Suzuki, & Takeuchi, ), Atlantic halibut Hippoglossus hippoglossus (Mazorra et al, ), rice field eel Monopterus albus (Zhou, Wu, Zhu, & Yan, ), Senegalese sole Solea senegalensis (Norambuena, Estévez, Carazo, & Duncan, ; Norambuena, Estévez, et al, ; Norambuena, Morais, et al, ) and Atlantic cod Gadus morhua (Norberg et al, ). ARA in broodstock diets has been reported to affect the spawning performance, egg quality, gonadal steroidogenesis and offspring quality.…”
Section: Introductionmentioning
confidence: 99%